2014
DOI: 10.4103/2249-4863.137663
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection among patients with upper gastrointestinal symptoms: prevalence and relation to endoscopy diagnosis and histopathology

Abstract: Aim:To determine the prevalence of H. pylori based on endoscopic biopsy and to investigate the association between H. pylori and endoscopy diagnosis and histopathological diagnosis.Materials and Methods:Over a period of two years, 228 endoscopic biopsies were included. Endoscopy diagnosis, histopathological diagnosis, and colonization with H. pylori were recorded and compared using appropriate statistical tests.Results:The overall prevalence of H. pylori was 68%; 69.6% in males and 66.7% in females. Duodenal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 15 publications
3
22
2
1
Order By: Relevance
“…Although it was varied between studies (16.3–70.5 %) [1419], we confirmed the prevalence of H. pylori infection is 38.4 % (56/146) using several diagnostic test that significantly related to source of drinking water [20]. The majority of strains are so-called Western-type- cagA in Nepal as similar to typical South Asian patterns [20].…”
Section: Introductionsupporting
confidence: 74%
“…Although it was varied between studies (16.3–70.5 %) [1419], we confirmed the prevalence of H. pylori infection is 38.4 % (56/146) using several diagnostic test that significantly related to source of drinking water [20]. The majority of strains are so-called Western-type- cagA in Nepal as similar to typical South Asian patterns [20].…”
Section: Introductionsupporting
confidence: 74%
“…In the present study, the prevalence of H. pylori among patients with dyspepsia were 81.7%. This was higher than that reported by Alhussaini (14) (71.33%), Roshana et al (15) (68%) and Adlekha et al (16) (62.0%). Egypt is a multiracial country, the different races although living together, have exclusive habits and cultural practices peculiar to their own.…”
Section: Discussioncontrasting
confidence: 60%
“…Patients with chronic active gastritis and chronic follicular gastritis had higher frequency of Helicobacter Pylori positivity with incidence of 84.8% and 84.1% respectively. Higher incidence of Helicobacter Pylori were also seen in other studies done by Shrestha R et al 20 Other studies also identified association between ulcerative lesions and higher incidence of Helicobacter Pylori. [21][22][23] Study done by X Y Chen et al observed positive correlation with the prevalence and density of lymphoid follicles and aggregates with H pylori infection.…”
supporting
confidence: 70%
“…18 Reflux esophagitis was observed in 10% of the patients which was less than study conducted by Ercelep OB et al 19 Ulcerative lesions of stomach and duodenum was more common in males than in females as was observed in a study done by Shrestha R et al 20 Most common pathology in histopathology was chronic active gastritis (42.1%), followed by chronic persistent gastritis (38.2%), chronic follicular gastritis (19.1%) and gastric carcinoma (0.5%). This result was in concordance with other study.…”
contrasting
confidence: 40%
See 1 more Smart Citation